A Potential Biocontrol Agent Streptomycesviolaceusniger AC12AB for Managing Potato Common Scab - Sarwar, Arslan; Latif, Zakia; Zhang, Songya; Hao, Jianjun; Bechthold, Andreas (Frontiers in Microbiology, 2019)
Potato common scab (PCS) is an economically important disease worldwide. In this study we demonstrated the possible role of Streptomyces violaceusniger AC12AB in controlling PCS. Isolates of Streptomyces scabies were obtained from CS infected tubers collected from Maine USA, which were confirmed by morphological and molecular analysis including 16S rRNA sequencing and RFLP analysis of amplified 16S-23S ITS. Pathogenicity assays related genes including txtAB, nec1 and tomA were also identified in all S. scabies strains through PCR reaction. An antagonistic bacterial strain was isolated from soil in Punjab and identified as S. violaceusniger AC12AB based on 16S rRNA sequencing analysis. Methanolic extract of S. violaceusniger AC12AB contained azalomycin RS-22A which was confirmed by 1H and 13C-NMR, 1H/1H-COSY, HMBC and HMQC techniques. S. violaceusniger AC12AB exhibited plant growth promotion attributes including Indole-3-acetic acid production with 17 µgmL-1 titers, siderophores production, nitrogen fixation and phosphates solubilization potential. When tubers were inoculated with S. violaceusniger AC12AB, significant (P < 0.05) PCS disease reduction up to 90% was observed in greenhouse and field trials, respectively. Likewise, S. violaceusniger AC12AB significantly (P < 0.05) increased potato crop up to 26.8% in field trial. Therefore, plant growth promoting S. violaceusniger AC12AB could provide a dual benefit by decreasing PCS disease severity and increasing potato yield as an effective and inexpensive alternative strategy to manage this disease